Edukasi Faktor Risiko dan Pencegahan Stroke Non-Hemoragik bagi Kader Kesehatan - Damayanti, Khavifah Intan; Khasanah, Suci; Cahyaningrum, Etika Dewi (Kolaborasi: Jurnal Pengabdian Masyarakat, 2025)
Introduction: Non-hemorrhagic stroke occurs due to obstruction of blood flow to the brain by a blood clot, with risk factors including hypertension, smoking, dyslipidemia, diabetes mellitus, obesity, and heart disease. Prevention can be achieved through health education. Objective: This community service activity aims to increase the knowledge and interest of cadres in stroke prevention through risk factor education. Method: This activity received ethical approval from the Research Ethics Committee of Universitas Harapan Bangsa (No. B.LPPM-UHB/722/05/2025) and was conducted in Karangaren Village, Purbalingga Regency, involving 15 health cadres. The activity consisted of three stages: preparation (pre-survey, obtaining permissions, and developing educational media and instruments), implementation (pre-test, interactive education using leaflets and PowerPoint, and post-test), and evaluation (assessing knowledge improvement and cadres’ interest in disseminating stroke prevention information). All activities were carried out in three sessions on May 14, 18, and 19, 2025. Result: The results showed an increase in knowledge from an average of 67.3% to 84.6% (a 25.8% increase), as well as high (100%) interest from cadres in educating the public. Conclusion: Health education effectively increases cadre understanding and interest, which is expected to support ongoing stroke prevention efforts. Practically, trained cadres can actively disseminate information on risk factors and preventive measures within the community, contributing to early detection, lifestyle modification, and reduced incidence of stroke.